STRATEGI MENGAJAR MATEMATIKA DENGAN PEMBELAJARAN SOSIAL EMOSIONAL DI SEKOLAH DASAR - Agusdianita, Neza; Heryanto, Debi; Yusnia, Yusnia; Maghfira Izzannia, Rizqa Dwi Shofiya; Ramadhani, Muhammad Habib (Prosiding Temu Ilmiah Nasional Guru, 2026)
This article discusses the integration of Social-Emotional Learning (SEL) into mathematics instruction in primary schools, which serves to enhance student learning outcomes. Amidst the challenges of implementing government-mandated curricula, this study indicates that students’ social and economic backgrounds significantly impact their mastery of mathematical concepts. Therefore, teaching strategies that prioritize the social-emotional dimension are given precedence.Based on a literature analysis, interactive and collaborative approaches have been proven to boost student motivation and engagement, as well as contribute to the development of student character within a supportive learning environment. Research suggests that the development of students’ social-emotional competencies directly correlates with their ability to solve complex mathematical concepts. The integration of technology in teaching in the digital era is also revealed as a key factor in creating engaging and dynamic learning experiences.Thus, an instructional model that blends SEL with innovative methods and technology utilization needs to be implemented effectively to prepare students to face future academic challenges. These overall findings underscore the necessity for sustained research to support educators in discovering relevant and efficient teaching strategies within the context of contemporary education.